Artisans Abroad British Migrant Workers in Industrialising Europe, 1815-1870 - Bensimon, Fabrice (Oxford University Press, 2023)
Between 1815 and 1870, when European industrialisation was in its infancy and Britain enjoyed a technological lead, thousands of British workers emigrated to the Continent. They played a key role in several sectors such as textiles, iron, mechanics, and the railways. These men and women thereby contributed significantly to the industrial take-off in continental Europe. This book examines the lives and trajectories of these workers, who emigrated from manufacturing centres in Britain to France, Belgium, Germany, and other countries. It is interested in their mobilities, their culture, their politics, and their relations with the local populations. It reminds us that the British economy was not just orientated towards the Empire and the United States, but also towards the Continent, long before the European Union and Brexit. It shows how critical the part played by migrant workers in the industrial revolution was. Artisans Abroad is the first social and cultural history of this forgotten migration.